Development of Incident Investigation Model for Process Safety Management Compliance - Mohd Subri, Mohd Syauqi (Universiti Teknologi PETRONAS, 2016)
Catastrophic industrial incidents continue to take place even after the proclamation of Process Safety Management (PSM) with its purpose is to deter incident like the Bhopal disaster in 1984 from reoccurring. Incident investigation element of PSM standard, 29 CFR 1910.119(m) outlines the requirements for identification of catastrophic incident, incident investigation team setup, report writings, follow-up actions on the established recommendations, communication of incident investigation findings with relevant personnel, and report recordkeeping. However, the implementation of the standard is subject to individual’s interpretation because it is a performance-based standard, which is likely to lead to PSM standard noncompliance issues.